Potensi Desa Wisata Lerep: Alternatif Penggerak Ekonomi Masyarakat Lokal - Khotimah, Maharani Chusnul; Rochaniah, Ana Naila; Faidah, Aulia Fikri; Octaviani, Rasti Amalia; Ningsih, Widyawati (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The development of a tourist area can have a positive impact on the economy of local communities. Like the Lerep Tourism Village in Semarang Regency. This tourist village has significant potential to be developed as an economic driver for the local community. This village optimizes natural, cultural and local resources to attract visitors. The aim of this research is to determine the potential of the Lerep Tourism Village and the developments that have been carried out or are still being planned. The research method used is qualitative research whose data comes from observations and in-depth interviews with several sources. This research describes the profile of Lerep Tourism Village and identifies opportunities and challenges in developing this tourism village. The village potential discussed includes natural tourism, education, culinary, culture and homestay accommodation. Apart from that, innovation and cooperation between local communities and the government are the main factors in maintaining the sustainability of the development of this tourist village.